Molecular phylogeny of the butterfly tribe Baorini Doherty, 1886 (Hesperiidae, Hesperiinae) in China - Jiang, Weibin; He, Haiyan; Li, Yuanyuan; Wang, Ying; Ge, Chen; Zhu, Jianqing; Yu, Weidong (Zootaxa, 2019)
The butterfly tribe Baorini Doherty, 1886 is a large group of skippers. In this study, a total of 8 genera and 41 species of putative members of this tribe, which represent most of the generic diversity and nearly all the species diversity of the group in China, were sequenced for two mitochondrial genes and three nuclear genes (2084 bp). Phylogenetic relationships and subdivision of this tribe were investigated and the status of the genera are discussed. Partitioned maximum likelihood analyses were performed based on the combined dataset. Our results suggest that the data are split into two well-supported clades in the phylogeny tree. This analysis also represents the most complete phylogenetic analysis of the tribe Baorini in China to date, and includes several genera and species that have been previously excluded from published phylogenies of this group.